Karakteristik Fisik, Kimia dan Organoleptik Pancake Menggunakan Tepung Premiks Ampas Kelapa dan Tepung Mocaf - Silvia, Setyorini; Wibisono, Yossi (Politeknik Negeri Jember, 2024)
Wheat flour is widely used by Indonesians as a basic ingredient for making bread, triggering the ever-increasing import of wheat flour. Therefore, it is necessary to have other alternatives to reduce dependence on the use of wheat flour. One of them is the utilization of coconut pulp waste which is processed into flour and then processed into pancakes with nutritional value and good quality. The purpose of this study was to analyze the effect of the addition of coconut pulp flour on the physical, chemical and organoleptic characteristics of pancakes and determine the best formulation in making pancakes. This study used a Randomized Group Design consisting of 5 treatments (0%, 10%, 20%, 30%, 40%). The results showed that coconut pulp flour gave a significantly different effect on fiber content, texture, specific volume, color a, color b and hedonic test as evidenced by further tests using the Duncan test at the 1% level. While the water content, ash content and color L test showed no significant difference.